2010
DOI: 10.4067/s0717-95022010000100038
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Changes in the Placenta in Pregnancies Complicated with Diabetes

Abstract: Placenta is the most accurate record of the infant prenatal experience. After delivery if the placenta is examined minutely, it provides much insight into the prenatal health of the baby and the mother. In diabetic pregnancy, placental weight is higher in comparison to normal pregnancy. To study the cellular differences that might contribute to larger size of placenta, light microscopic analysis was performed on 25 full term placentas, out of which 20 were of Gestational diabetes mellitus (12 controlled on die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 16 publications
9
15
0
Order By: Relevance
“…Thismacrosmiamay be attributed to fetal hyperinsulenemia in response to hyperglycaemia infetuses of diabetic mothers [1,3,15]. The interesting point in the present study that, there are no significant differences of these parameters in GDM group controlled by diet without insulin and control group.Similar findings were reported inprevious study by Verma et al (2010) [8]. In the same track, several differences were identified in the lightmicroscopy of terminal villi from the placentae of GDM group controlled with insulin; large number of syncytial knots(Increased number of syncytiotrophoblastnuclei which showed chromatin clumping, a feature typical of senescence,and were usually arranged in clusters known as syncytialknots as defined by Jone& Fox, 1977 [11]),fibrinoid necrosis, villous edema, villous fibrosis andproliferation of the capillaries.While placentas of GDMgroup controlled with diet alone without insulin showed minimally increased number of syncytialknots,fibrinoid necrosisand none of them showed villous edema,villous fibrosis or fetal capillary proliferationresemblingmore to the control group.More or less similar results were found in previous old studies (16,17) where they found in addition fibrin necrosis and thickening of basal membrane of trophoblast in the placentaof poorly controlled diabetes.In our study, all the patients were perfectly controlled whatever the used modality with insulin or without.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Thismacrosmiamay be attributed to fetal hyperinsulenemia in response to hyperglycaemia infetuses of diabetic mothers [1,3,15]. The interesting point in the present study that, there are no significant differences of these parameters in GDM group controlled by diet without insulin and control group.Similar findings were reported inprevious study by Verma et al (2010) [8]. In the same track, several differences were identified in the lightmicroscopy of terminal villi from the placentae of GDM group controlled with insulin; large number of syncytial knots(Increased number of syncytiotrophoblastnuclei which showed chromatin clumping, a feature typical of senescence,and were usually arranged in clusters known as syncytialknots as defined by Jone& Fox, 1977 [11]),fibrinoid necrosis, villous edema, villous fibrosis andproliferation of the capillaries.While placentas of GDMgroup controlled with diet alone without insulin showed minimally increased number of syncytialknots,fibrinoid necrosisand none of them showed villous edema,villous fibrosis or fetal capillary proliferationresemblingmore to the control group.More or less similar results were found in previous old studies (16,17) where they found in addition fibrin necrosis and thickening of basal membrane of trophoblast in the placentaof poorly controlled diabetes.In our study, all the patients were perfectly controlled whatever the used modality with insulin or without.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the mean placental weight, the mean placental diameter, the mean placental central thickness and the mean placental surface area in GDM group controlled with insulin was more as compared to control group and this difference was found highly significant (p < 0.01). Similar findings were reported inprevious studies by Verma et al (2010) [8],Chowdhury et al (2011) [13] and Saha et al (2014) [14]. The weight gain in placentae ofdiabetic mothers may be attributed tomacrosomia andcompensatory hyperplasia.Macrosomia affects the fetus and fetal part ofplacenta.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…11 Marilza VC et al found mean birth weight 3490 gms. In the present study mean birth weight was 3560 gm.…”
Section: Diabetes Mellitusmentioning
confidence: 99%